2008
DOI: 10.1590/s1519-69842008000400013
|View full text |Cite
|
Sign up to set email alerts
|

Attachment of the peritrich epibiont Zoothamnium intermedium Precht, 1935 (Ciliophora, Peritrichia) to artificial substrates in a natural environment

Abstract: Peritrich ciliates are commonly found as epibionts, colonizing living organisms, or attached to non-living substrates in freshwater, estuarine and marine environments. Several species of peritrich epibionts are obligate, which means that they are able to only colonize other organisms, while others are facultative attaching to living or non-living substrates. The peritrich Zoothamnium intermedium is commonly found as epibiont on the copepod species Acartia tonsa and Eurytemora affinis in Chesapeake Bay, USA. Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Additionally, the high individual clearance rate and ingestion rate of the epibionts mean that each ciliate processed a large amount of bacterial biomass. Utz (2008) reported that at a food concentration of 10 6 bacteria ml −1 , comparable to our experimental food concentrations, the epibiont ciliate Zoothamnium intermedium attained a growth rate as high as 0.8 day −1 . An even higher in situ growth rate (1.37 day −1 ) has been reported for benthic peritrich ciliate (Kusuoka and Watanabe, 1987).…”
Section: Discussionsupporting
confidence: 84%
“…Additionally, the high individual clearance rate and ingestion rate of the epibionts mean that each ciliate processed a large amount of bacterial biomass. Utz (2008) reported that at a food concentration of 10 6 bacteria ml −1 , comparable to our experimental food concentrations, the epibiont ciliate Zoothamnium intermedium attained a growth rate as high as 0.8 day −1 . An even higher in situ growth rate (1.37 day −1 ) has been reported for benthic peritrich ciliate (Kusuoka and Watanabe, 1987).…”
Section: Discussionsupporting
confidence: 84%
“…Many sessile organisms are known as substrate specialists, especially in the case of obligate epibionts (Bordeaux & Brett, 1990; Callaway, Reinhart, Moore, Moore, & Pennings, 2002; Fontaneto & Ambrosini, 2010; Frick, Kopitsky, Bolten, Bjorndal, & Martins, 2011; Matsuyama, Aruga, & Tanaka, 1999; Utz, 2008). In relying upon naturally limited spatial niches, epibionts need to cope with changing conditions of substrates, depending on host morphology, behavior and growth (e.g., Abbott & Bergey, 2007; Bell, 2005; Callaway et al, 2002; Fontaneto & Ambrosini, 2010; Pfaller, Bjorndal, Reich, Williams, & Frick, 2008; Vasconcelos, Cúrdia, Castro, & Gaspar, 2007; Wagner & Zotz, 2020; Woods, Cardelús, & DeWalt, 2015).…”
Section: Introductionmentioning
confidence: 99%